A case of fatal invasive aspergillosis in a patient with neurosarcoidosis treated with infliximab. (3rd June 2019) - Van Sanford, Carson; Obeidat, Ahmed Z.; Hagen, Matthew; Zabeti, Aram
Abstract: Introduction: CNS involvement in sarcoidosis is seen in 5–10% of cases. Long term treatment involves steroids and other immunomodulatory agents, including infliximab. Chronic immunosuppression can result in increased patient susceptibility to opportunistic infections. We present a case of fatal aspergillosis in a patient with neurosarcoidosis treated with infliximab. Case report: A 55-year-old woman with neurosarcoidosis on infliximab (started 4 months prior) and dexamethasone, presented with progressive cognitive decline. Exam revealed impaired attention and disorientation with preserved language. Brain MRI showed multiple, bilateral cortical and subcortical ring-enhancing lesions. We held immunosuppression due to suspicion of infection; empiric Amphotericin B was given early in the hospital course. The patient rapidly deteriorated from a neurological and respiratory standpoint, requiring intubation. CSF analysis showed elevated protein of 511 and normal glucose of 104 (67% serum), with lymphocytic pleocytosis (25 cells, 96% lymphocytes). Systemic and CNS microbiological studies were negative. On hospital day 13, bronchial fluid grew Aspergillus fumigatus, prompting a switch to voriconazole. Despite early empiric antifungal treatment, she died from respiratory failure; autopsy revealed systemic and CNS aspergillosis with multiple brain abscesses. Discussion: This case represents an example of a fatal complication of infliximab therapy, which was recently shown to be effective in neurosarcoidosis in one study. It also serves to highlight the challenges faced in diagnosing ring-enhancing lesions, especially in patients with pre-existing brain disorders. Finally, it highlights the difficulty in treating invasive aspergillosis. Further studies are needed to identify risks associated with infliximab therapy and potential early interventions to improve outcomes.